THE RELATIONSHIP OF MOTHER'S EDUCATION AND OCCUPATION TO STUNTING EVENTS IN TODDLERS - Ramadhana Adla; Siti Maisyaroh Fitri Siregar; Arfah Husna (RADJA PUBLIKA, 2022)
In view of the aftereffects of Septamarini's exploration in the Journal of Nutrition College in 2019 said that mothers with low education and knowledge are at risk of having stunted children. Working mothers cannot take care of their children so this can be one of the risk factors for children to experience stunting and according to the 2019 SSGBI report states that the prevalence of stunting in kids under five, especially in Aceh province is 21.9%, West Aceh district is 24.5% . The high pervasiveness of stunting in youngsters under five in West Aceh is one of the general medical issues that must be addressed so as not to adversely affect the quality of the nation's generation of resources. Research objectives: This review intends to decide the connection among education and mother's occupation on the occurrence of stunting in kids under five years of age in Kawai XVI District. Research method: This examination utilizes insightful exploration technique with cross sectional strategy. The populace in this review were moms who had kids under five in Kawai XIV District. Information investigation in this review incorporates univariate examination, and bivariate examination. Results: The outcomes got that there is a huge connection between maternal schooling and the frequency of stunting p-value: 0.043 furthermore there is no critical connection between mother's work and the frequency of stunting in toddlers with p-value: 0.086.